Effect of Piperine on the Metabolism and Pharmacokinetics of Carbamazepine in Healthy Volunteers - Bedada, S. K.; Appani, R.; Boga, P. K. (Drug Research, 2017)
Carbamazepine (CBZ) is a widely used antiepileptic drug with narrow therapeutic window and it may be prone to drug interactions. The purpose of present study was to investigate the effect of PIP on metabolism and pharmacokinetics of CBZ in healthy volunteers. An open-label, 2 period, sequential study was conducted in 12 healthy volunteers. PIP 20 mg was administered once daily for 10 days during treatment phase. A single dose of CBZ 200 mg was administered during control and after treatment phases under fasting conditions. The blood samples were collected after CBZ dosing at predetermined time intervals and analyzed by LC-MS/MS method. Treatment with PIP significantly enhanced maximum plasma concentration (Cmax), area under the curve (AUC) and half life (T1/2) of CBZ by 68.7, 47.9 and 43.2%, respectively as compared to control. On the other hand, elimination rate constant (Kel) and apparent oral clearance (CL/F) of CBZ were significantly decreased by 23.8 and 38.9%, respectively upon PIP treatment as compared to control. Furthermore, PIP treatment significantly decreased metabolic (CBZE/CBZ) ratios of Cmax and AUC, indicating the decreased formation of CBZ to CBZE. The results suggest that the altered CYP3A4 enzyme activity and pharmacokinetics of CBZ might be attributed to PIP mediated inhibition of CYP3A4 enzyme. Thus, there is a potential pharmacokinetic interaction present between PIP and CBZ. Accordingly, caution should be taken when PIP is used in combination with therapeutic drugs metabolized by CYP3A4 in addition to CBZ.
Keywords: carbamazepine; piperine; CYP3A4 enzyme; pharmacokinetics; metabolism; bioavailability